Hopes and fears regarding care robots: Content analysis of newspapers in East Asia and Western Europe, 2001–2020 - Kodate, N.; Maeda, Y.; Hauray, B.; Tsujimura, M.; Chan, W. C. H.; Mannan, H.; Yu, W.; Dalgalarrondo, S.; Cheung, M. C.; Yumoto, A.; Suwa, S.; Donnelly, S.; et al. (Frontiers in Rehabilitation Sciences, 2022)
As a type of welfare technology, care robotics is now widely seen as a potential aide to rehabilitation, increasing independence and enhancing the wellbeing of people with disabilities and of older adults. Research into and development of care robots have both been vigorously promoted in North America, Europe and Asia, and the competition for technological advancement in robotics is becoming fierce. AI ethics and policy guidelines are being established. However, there are still differences in attitudes and perceptions, as well as national policies regarding this type of welfare technology. Moreover, despite the anticipated usefulness, it is believed that progress has been slow in the diffusion of care robots. In order to explore how public discourses support technological innovation, such as care robots, while preparing society for potential risks and impact, we sought to ascertain whether public discourse on care robots varies from region to region. For example, what are the hopes and promises associated with care robots and what are the concerns? To address these questions, this article explored how care robots have been portrayed in five major broadsheet newspapers in five jurisdictions in Asia and Europe (France, Great Britain, Hong Kong SAR, Ireland and Japan). We obtained 545 articles for the period between January 2001 and September 2020, more than half of which originated in Japan. A thematic analysis was conducted of these articles written in four languages (Chinese, English, French and Japanese). Positive and negative narratives were teased out, alongside other key prominent themes identified, such as Japan as the land of robots, the pandemic, and the impact of robots on the economy. As the number of robot-related articles grew from the year 2012 onwards, narratives became more nuanced in European newspapers, but not in Asian ones. Furthermore, recent articles began to address the social and relational impact of care robots, while providing concrete examples of improvements in the quality of life of users Further careful examination will be necessary in the future in order to establish the impact of robotics use in rehabilitation for people with disabilities, older adults, their carers and society at large.